Analysis of the Position of Special Envoy of the President for the Development of Young Generation and Art Workers in Indonesia Based on Constitutional Law - Darwin D.P.G. Marbun; Janpatar Simamora; Hisar Siregar (Dinasti Research, 2025)
This study aims to analyze the legal position of the Special Envoy of the President in the field of fostering young people and art workers based on the perspective of Indonesian constitutional law. The existence of the position of Special Envoy of the President in the Indonesian constitutional structure, especially in the context of empowering the younger generation and strengthening the creative industry, raises juridical questions regarding its legal basis, authority, and accountability. Using a normative juridical legal research method with a statutory approach, this research examines Presidential Decree Number 76/M of 2024 which regulates the appointment of special envoys of the President in the 2024-2029 period, as well as the relevance of these regulations within the framework of Indonesian constitutional law. The results show that although the special envoy of the President has a strategic role in supporting the development of young talents and the creative industry sector, the position lacks a clear and specific legal basis, which can lead to problems in terms of accountability and transparency. Therefore, this study recommends the need for the drafting of firmer regulations regarding the position, duties, and authority of special envoys, as well as strengthening supervision and coordination mechanisms with relevant ministries or institutions. This is expected to increase the effectiveness and contribution of special envoys to the progress of the Indonesian nation, especially in the development of the creative economy.